2006
DOI: 10.1071/zo05020
|View full text |Cite
|
Sign up to set email alerts
|

Variation in population structure across the ecological range of the Queensland fruit fly, Bactrocera tryoni

Abstract: We sampled a pest fruit fly species, the Queensland fruit fly, Bactrocera tryoni, across its entire ecological range in eastern Australia, from ancestral high-density populations in tropical regions through to isolated outbreak populations in marginal arid areas. Using DNA microsatellite markers, we found that in ancestral areas, population differentiation was low and populations were genetically homogeneous over large distances. In more temperate areas, populations were far more genetically differentiated but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 27 publications
2
27
1
Order By: Relevance
“…The unanticipated feature of our results was the cline in microsatellite allele frequencies. Earlier studies of central populations of B. tryoni showed minimal genetic differentiation between populations spread over almost 3000 km of tropical Australia (Yu et al, 2001;Gilchrist et al, 2006). Consequently, the microsatellite cline identified here, which covers the southern 500 km of the species range, was unexpected.…”
Section: Discussionsupporting
confidence: 38%
See 3 more Smart Citations
“…The unanticipated feature of our results was the cline in microsatellite allele frequencies. Earlier studies of central populations of B. tryoni showed minimal genetic differentiation between populations spread over almost 3000 km of tropical Australia (Yu et al, 2001;Gilchrist et al, 2006). Consequently, the microsatellite cline identified here, which covers the southern 500 km of the species range, was unexpected.…”
Section: Discussionsupporting
confidence: 38%
“…Site 1 appears to be at the edge of an abrupt transition zone where the homogeneous central populations give way to fragmented town-based populations. A preliminary survey of the towns in the present study area showed higher levels of genetic differentiation between towns (0.01oF ST o0.12; Gilchrist et al, 2006). In contrast to the central populations, the inland populations appear to have a metapopulation structure approaching the current southern species border.…”
Section: B Tryoni Population Expansioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Originally, endemic to the tropical rainforests of north-eastern Australia (Gilchrist et al, 2006), its successful spread to cultivated fruit and vegetables (Lewontin and Birch, 1966) saw a subsequent rise to pest status. The polyphagous nature of this pest, climatic suitability and the expansion of its cultivated host range have, among other factors, enabled its spread throughout eastern Australia.…”
Section: Introductionmentioning
confidence: 99%